Aristotle's metaphysics Lambda : annotated critical edition based upon a systematic investigation of Greek, Latin, Arabic and Hebrew sources - Alexandru, Stefan, 1966- (Philosophia antiqua., 2013)
In this annotated critical edition of Aristotle's Metaphysics Lambda Stefan Alexandru draws upon many hitherto unexplored sources of the direct and indirect tradition, inter alia upon an independent Greek manuscript he has discovered in the Vatican Library.